Peranan Fungi Mikoriza Arbuskular (FMA) dan Serasah Daun Gamal (Gliricidia sepium L.) terhadap Pertumbuhan Bawang Merah (Allium cepa L.) pada Tanah Podzolik Merah Kuning - Supeni Sufaati; Rr. Evi D. Aryuni (Jurnal Biologi Papua, 2009)
The aim of study was to know the effect of Arbuscular Mycorrhiza Fungi (AMF), Glomus mosseae on the growth of onion Allium cepa L. on red-yellow podzolic soils. Completely Randomized Design (CRD) factorial with 10 replicates was used in this experiment. The first factor was mycorrhizae, with two level: without inoculation as a control (M0); 10 gram inoculation = M1). The second factorwas leaf litter of gamal Gliricidia sepium L. species   wich were no litter as S0; 5 gram litter = S1; S2 was 10 gram of litter; and 20 grams of loitter in one kilogram of soil separately. Parameters used in this study were the growth of onion that has infected root in percent, and Relative Growth Rate (RGR). ANOVA was used to analyze the data, and followed with DMRT at 95% level test. The result showed that mycorrhizal inoculation increased root and shoot fresh weight, the dry weight of shoot; and the percentage of root infection on the onion. While the leaf litter of gamal increased only in leaf area. In contrast mycorrhizal inoculation and gamal leaf litter and their combination had no effect on other growth parameters. Key words: AMF, Glomus mosseae, Gliricidia sepium, Allium cepa.